Bacterial Cyclic Dinucleotides and the cGAS–cGAMP–STING Pathway: A Role in Periodontitis? - Elmanfi Samira; Yilmaz Mustarfa; Ong Wilson WS; Yeboah Kofi S; Sintim Herman O; Gürsoy Mervi; Könönen Eija; Gürsoy Ulvi K. (Switzerland, 2022)
Host cells can recognize cytosolic double-stranded DNAs and endogenous second messengers as cyclic dinucleotides-including c-di-GMP, c-di-AMP, and cGAMP-of invading microbes via the critical and essential innate immune signaling adaptor molecule known as STING. This recognition activates the innate immune system and leads to the production of Type I interferons and proinflammatory cytokines. In this review, we (1) focus on the possible role of bacterial cyclic dinucleotides and the STING/TBK1/IRF3 pathway in the pathogenesis of periodontal disease and the regulation of periodontal immune response, and (2) review and discuss activators and inhibitors of the STING pathway as immune response regulators and their potential utility in the treatment of periodontitis. PubMed/Medline, Scopus, and Web of Science were searched with the terms "STING", "TBK 1", "IRF3", and "cGAS"-alone, or together with "periodontitis". Current studies produced evidence for using STING-pathway-targeting molecules as part of anticancer therapy, and as vaccine adjuvants against microbial infections; however, the role of the STING/TBK1/IRF3 pathway in periodontal disease pathogenesis is still undiscovered. Understanding the stimulation of the innate immune response by cyclic dinucleotides opens a new approach to host modulation therapies in periodontology.